2010
DOI: 10.1007/s10608-010-9306-2
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Negative and Positive Thoughts in Children: An Adaptation of the Children’s Automatic Thoughts Scale (CATS)

Abstract: The aim of this study is to describe the factor structure and psychometric properties of an extended version of the Children’s Automatic Thoughts Scale (CATS), the CATS-Negative/Positive (CATS-N/P). The CATS was originally designed to assess negative self-statements in children and adolescents. However, positive thoughts also play a major role in childhood disorders such as anxiety and depression. Therefore, positive self-statements were added to the CATS. The CATS-N/P was administered to a community sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 34 publications
1
42
0
12
Order By: Relevance
“…In addition, negative and positive automatic thoughts were measured using the Children's Automatic Thoughts Scale-Negative/Positive (CATS-N/P; Hogendoorn et al, 2010).…”
Section: Case Examplementioning
confidence: 99%
“…In addition, negative and positive automatic thoughts were measured using the Children's Automatic Thoughts Scale-Negative/Positive (CATS-N/P; Hogendoorn et al, 2010).…”
Section: Case Examplementioning
confidence: 99%
“…This group participated in a validation study of the Children's Automatic Thoughts Scale-Negative/Positive (CATS-N/P). Detailed sample characteristics of this group are described elsewhere (Hogendoorn et al, 2010). Children in this group were screened for emotional problems with the SDQ (Strength and Difficulties Questionnaire, Goodman, 1997;Dutch version Van Widenfelt et al, 2003) and the STAIC-trait (Spielberger State Trait Inventory for Children-trait subscale; Spielberger, Edwards, Lushene, Montuori, & Platzek, 1973).…”
Section: Participantsmentioning
confidence: 99%
“…Schniering and Rapee [24] found no significant differences between children aged 7-11 years and adolescents aged 12-16 years on any of the subscales of the CATS. In contrast, Hogendoorn et al [28] found that children aged 8-11 years reported more negative thoughts related to threat and failure than adolescents aged 12-18 years.…”
Section: Introductionmentioning
confidence: 88%
“…For example, boys report more hostile thoughts than girls [24,28], while girls report more social threat and failure thoughts than boys [24]. Age effects have been less consistent.…”
Section: Introductionmentioning
confidence: 95%